MongoDB High Availability. - Mehrabani, Afshin (Birmingham : Packt Publishing, Limited, 2014)
This book has a perfect balance of concepts and their practical implementation along with solutions to make a highly available MongoDB server with clear instructions and guidance. If you are using MongoDB in a production environment and need a solution to make a highly available MongoDB server, this book is ideal for you. Familiarity with MongoDB is expected so that you understand the content of this book.
Understanding monitoring strategies -- Utilizing the profiling feature -- Utilizing the built-in reporting tools -- mongotop -- mongostat -- Enabling the web-based console -- Understanding the reporting commands -- Executing a command -- Utilizing the dbStats command -- Utilizing the collStats command -- Understanding the serverStatus command -- Utilizing the replSetGetStatus command -- Using database logs -- Introducing web-based utilities -- Utilizing the MMS monitoring service -- Understanding Scout -- Utilizing server density -- Utilizing LogicMonitor -- Introducing FusionReactor -- Introducing self-hosted utilities -- Summary -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: MongoDB; C++ (Computer program language).; Electronic books